The effect of general cooling of homeothermic organism on the erythrocyte and leukocyte indices of the blood - Lomako, V. V.; Pyrozhenko, L. N.; Sylo, O. V. (Ukrainian Antarctic Journal, 2017)
The objectives of the study were the investigation of reactions of the erythrocyte and leukocyte links of rat’s blood under general immersion hypothermia (IH). Methods. The IH was simulated by “forced swimming” test in cold water (0°C, 5 min, down to 27°C). The dynamics of erythrocyte transformation and distribution of their shapes were studied by a small-angle light scattering method. The types and number of leukocytes were determined in blood smears. The transformation indices of erythrocytes (ITE) and integral leukocyte indices (ILI) were calculated. Results. Under IH a decrease in the number of discocytes and an increase in erythrocytes altered forms were observed; the values of transformation indices, reversible and irreversible transformations were increased. The development of IH was accompanied by leukocytosis and a decrease in the number of segmented neutrophils on the background of the stab cells increase. The young, plasmatic and polychromatophilic cells as well as cytoplasm plasmatization in single leukocytes were noted. Calculation of ILI revealed activation in tissue destruction processes, immediate type of hypersensitivity and an increase in the Garkavi adaptation index. On the contrary, 24 hrs after the IH, the proportion of the discocytes increased on the expense of highly resistant flattened discocytes appearance, and the proportion of altered cells decreased due to their elimination from the blood. The values of the indices of transformation, reversibility and reversible transformation were decreased, but the index of irreversible transformation has increased by an order of magnitude. Twenty four hrs after the IH, the leukocytosis and the increase in the stab neutrophils against the background of lymphopenia as well as the appearance of young cell forms, polychromatophils and plasmatic cells were noted. Changes in ILI indicated the activation of the cellular link of the immune system, specific defense cells, delayed type hypersensitivity processes and macrophage system components, tissue decay processes, intoxication and allergisation. Conclusions. General immersion hypothermia significantly altered the quantitative and qualitative ratios of the shapes and types of blood cells in rats, affected the processes of erythrocyte transformation and the activation of distinct immunity links (according to the calculation of ITE and ILI, respectively). The direction and intensity of these changes depend on the terms of observation (immediately and 24 hrs after cooling).